Trends in Research on the History of Cooperativism and the Social and Solidarity Economy in Latin America. Advances in Its Analysis and Interpretation; Tendencias en la Investigación de la Historia de la Economía Social en Iberoamérica. Avances en Su Análisis E Interpretación - Radrigan-Rubio, M (CIRIEC, 2025)
This paper reviews the background of historiographical production on cooperativism and the social and solidarity economy in Latin America. The aim is to review the state of the art in order to help show the trends and gaps in historical studies. The paper first reviews the different concepts involved in historical analysis: cooperatives and cooperativism, Social Economy, Solidarity Economy, and Social and Solidarity Economy. Subsequently, a detailed review of the historiographical production in Latin America, Spain, and Portugal is made. Thus, this section presents a description of the first historical studies on the cooperative sector, highlighting the work related to the creation and development of the first cooperative in England known as the Equitable Pioneers of Rochdale in 1844. At the same time, this section presents a comparative table that accounts for the main historical studies on the social economy and cooperativism in countries such as Argentina, Mexico, Colombia, Brazil and Chile, among other countries. Finally, and by way of conclusion, a summary is provided and a medium- and longterm research agenda is proposed to fill existing gaps and promote collective comparative research. © (2024), (CIRIEC). All Rights Reserved.